Musculoskeletal emergencies - Browner, Bruce D.; Fuller, Robert 1964 (Elsevier/Saunders, 2013)
Equip yourself with all the guidance you need to diagnose, stabilize and provide the initial management of MSK emergencies as effectively as possible. Optimize patient's disposition ranging from emergency department discharge to the operating room. A leading orthopaedic trauma surgeon and a respected emergency physician bridge the gap between these specialties to help you give these patients the best chances of favorable outcomes.